Novel shape memory materials - Wei, Jun. (2010)
In this report, a novel shape memory material is investigated and demonstrated. This material is an extension of silicone based thermo-responsive shape memory hybrid (SMH) that was investigated by Ding Zhen in his PhD study and this author in the URECA project. Melt glue is added into silicone as filler to form this new SMH, named silicone-melt glue (SMG) SMH. Various samples are fabricated and characterized including shape memory test, cyclic tensile test, self-healing test, etc. This material has typical shape memory phenomenon, namely being able to recover from a temporary shape to its original shape. Besides the shape memory effect, as compared with other shape memory materials, this SMH has excellent elasticity property, just rubber band. In addition, it has self-healing function which is not possible in silicone-wax SMH in our previous study. All these properties are demonstrated in the project and presented in this report.